Analisis Kualitas Butir Soal Penilaian Akhir Semester Ganjil Kelas III Tema 1 SDN Mulyoagung IV Singgahan - Shofiyana, Aina; Rosyidah, Irma (Madrasah Ibtidaiyah Education Journal, 2024)
This research was motivated by the fact that an analysis of the quality of the questions on the examination test had never been carried out. The purpose of writing this thesis is to determine the level of difficulty, differentiating power, and distractors of questions on odd UAS class III theme 1 growth and development of living things. The method used in this research is concurrent embedded with qualitative methods as the primary method while quantitative methods are secondary. Data collection uses interviews, observation and documentation from school principals, teachers and administrative staff. Research results: 1) In terms of level of difficulty, there are 5 questions in the easy classification, 5 questions in the medium classification, and 5 questions in the difficult classification. 2) In terms of excellent discriminating power, there are 2 questions, 3 questions with good discriminating power, 0 questions with good discriminating power, 8 questions with poor discriminating power, and questions with poor discriminating power. Once there are 2 questions. In terms of level of difficulty there are 5 questions in the easy classification, 5 questions in the medium classification, and 5 questions in the difficult classification. 3) In terms of distractors, the questions in the very good classification are 2 question items located in question numbers 8 and 12. The question items in the good classification are 5 question items located in the numbers 3, 5, 7, 10, and 15. The question items in There are 6 questions in the poor classification located at numbers 1, 4, 6, 9, 11, and 13. There are 2 questions in the poor classification at numbers 2 and 12.